Persistence of malachite green and leucomalachite green in red tilapia (Oreochromis hybrid) exposedtodifferenttreatmentregimens - Kwan, Penz Penz; Banerjee, Sanjoy; Shariff, Mohamed; Md. Yusoff, Fatimah (Elsevier, 2020)
Abstract Malachite green (MG) is not permitted by the EU and FDA to be used in animals intended for human consumption due to its potential carcinogenesis. However, recent findings have shown residues of MG in fish sold to consumers. Therefore, the presence of MG residues is of concern. In this study, MG and its primary metabolite leucomalachite green (LMG) in red tilapia (Oreochromis hybrid) muscle tissue was quantified by a simplified method for sample preparation using liquid chromatography-tandem mass spectrometry. The decision limit and detection capability for MG was 0.05 μg/kg and 0.09 μg/kg and for LMG was 0.05 μg/kg and 0.08 μg/kg, respectively. In addition, accuracy, precision, recovery, and matrix effects were also performed. To evaluate the persistence of MG and LMG, fish were exposed to dip (A) (66.7 mg/L; 30 s), dips (B) (66.7 mg/L; 30 s repeated for 5 days), short-term bath (C) (6.7 mg/L; 15 min), short-term bath (D) (6.7 mg/L; 15 min repeated for 5 days) and long-term bath (E) (0.5 mg/L; 6 days) treatments using MG. The MG and LMG residues were quantified at the following intervals; immediately after treatment, 1st, 2nd, 3rd, 4th, 10th, 20th and 30th day post-exposure. Long-term bath (E) showed the highest accumulation of total MG and LMG immediately after treatment (441.38 μg/kg) and at day 30 (13.30 μg/kg). Whereas, all other treatments (day 30) were below 0.26 μg/kg.